Odpowiedzi

2009-11-20T15:40:58+01:00
Zapisz w prostej postaci :
7x²- 4x - 6x²+4-x²+5x= -x²+x+4

-2(3a-2b)-4a(2-3a+2b)=-6a+4b-8a+12a²-8ab=-6a+4b,
czyli 12a²-8a-8ab

(4-x)(2x+5)-4=8x+20-2x²-5x,
czyli -2x²+3x+20

(4-2x)(3x-3)-2x(3x+1)= 12x-12-6x²+6x-6x²+2x,
czyli -12x²+20x-12
1 1 1
2009-11-20T15:40:42+01:00
7x²- 4x - 6x²+4-x²+5x= x+4

-2(3a-2b)-4a(2-3a+2b)= -6a+4b-(8a-12a²+8ab)= -6a+4b-8a+12a²-8ab= =12a²-14a+4b-8ab

(4-x)(2x+5)-4= 8x+20-2x²-5x-4= -2x²+3x+16

(4-2x)(3x-3)-2x(3x+1)=12x-12-6x²+6x-(6x²+2x)= 12x-12-6x²+6x-6x²-2x=-12x²+16x-12
2009-11-20T16:00:19+01:00
7x²- 4x - 6x²+4-x²+5x=x+4

-2(3a-2b)-4a(2-3a+2b)=-6a+4b-8a+12a²-8ab=-14x+4b+12a²-8ab

(4-x)(2x+5)-4=8x+20-2x²-5x=3x+20-2x²

(4-2x)(3x-3)-2x(3x+1)= 12x-12-6x²+6x=18x-12-6x²